PENGARUH PENGETAUAN PERPAJAKAN DAN TAX MORALE TERHADAP NIAT PATUH PAJAK PADA GENERASI Z - Puspitasari, Imelda; Kurniawan, Febry; Abrar, Muhammad Daffa; Humairoh, Amanda Sevta; Linawati, Linawati (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the influence of Tax Knowledge and Tax Morale on Tax Compliance Intention among Generation Z in South Tangerang. A quantitative approach was employed using multiple linear regression analysis with the assistance of IBM SPSS Statistics version 27. The sample consisted of 100 Generation Z respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability testing, classical assumption testing, t-tests, and the coefficient of determination. The results indicate that Tax Knowledge has no significant effect on Tax Compliance Intention, while Tax Morale has a positive and significant effect on Tax Compliance Intention. These findings highlight that moral and ethical considerations play a more dominant role than technical tax knowledge in shaping the tax compliance intention of Generation Z.